Python 3 for Absolute Beginners - Hall, Hall (Apress, 2013)
If you are using Windows, you will probably have to install Python and configure certain settings correctly before you can get to grips with the examples in this book. For that, you will need to refer to the specific instructions for your operating system on the following Python web pages: • http://wiki.python.org/moin/BeginnersGuide/Download • http://www.python.org/doc/faq/windows/ • http://docs.python.org/dev/3.0/using/windows.html First, you need to download the official installer; alternative versions for Itanium and AMD machines are available from http://www.python.org/download/. You should save this file, which will have a .msi extension, somewhere you’ll be able to find again easily. You can then double-click this file to start the Python installation wizard, which will take you through the installation. It’s fine to accept the default settings if you’re not sure of any answer.